Social and Pedagogical Technology of Effective Organization of Students' Free Time - Ibragimova S.O. (International Journal on Orange Technologies, 2023)
In this article, the psychological and pedagogical theoretical foundations of organizing high school students' free time are widely covered, and the content of schoolchildren's free time is of a program nature and is aimed at the formation of a dynamic and sustainable cultural free time. space in society characterized.